ҚУЁШ ЭЛЕМЕНТИ ЭФФЕКТИВЛИГИГА ТАЪСИР ЭТУВЧИ ОМИЛЛАР ТАҲЛИЛИ - Исмайлов, К.А.; Кенжаев, З.Т.; Жалелов, М.А. (SCIENCE and SOCIETY, 2018)
The article deals with the analysis of the factors influencing on the CUA of the solar element. There are some conclusions how to in crease the effectiveness and the analysis of power loss of the falling eradiation by a solar element. The authors also studied the influence of the prohibited zones and defects on the CUA.